To Determine the Frequency and Risk Factors for Significant Postoperative Bleeding in Children with Congenital Heart Diseases Undergoing Open Heart Surgery in a Tertiary Care Center - Mohsina, Rajab Ali Khokar, Veena Kumari, Mujeeb Ur Rehman, Aliya Kemal Ahsan, Saad Bader Zakai, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency and risk factors for significant postoperative bleeding in children with congenital heart diseases undergoing open cardiac surgery in ​​our ​​tertiary ​​care ​​hospital. Methods: A prospective observational study was carried out in the department of Paediatric cardiac intensive care Unit at National Institute of Cardiovascular diseases Karachi between [dates here].Children aged 0-18 years underwent open heart surgery for congenital heart defects. Those patients who had previous palliative surgeries for congenital heart defects were included in the study.The duration of bleeding, recurrence, and treatment given (tranexamic acid bolus/infusion, platelets, FFPs, Packed RBC/WB, Factor 7 concentrates) were also documented. The outcome of bleeding was recorded as either stopped or persistent. If bleeding persisted, any other intervention needed was also noted. Results: The frequency of preoperative bleeding was found in 20 (13.0%) patients. In distribution risk factors among 20 postoperative bleeding patients, decreased LV function was not present, prolong bypass time was noted in 2(20.0%) & 8 (80.0%) as minor & major bleeding in patients, prolong cross clamp time 2 (28.6%) & 5 (71.4%), arrhythmia 1 (8.3%) & 11 (91.7%) and infection was noted in 2 (28.6%) & 5 (71.4%) as minor & major bleeding, postoperative intervention 3(50%) major & minor, chest intervention was 1(16.7%) & 5 (83.3%) as minor & major bleeding respectively. Mean preoperative bleeding showed LVEF% was 67.5%±0.1 while mean TAPSE was 20.9±14. Hemoglobin at presentation was 13.98±2.8 mg/dl while it decreased to 12.43±1.8 mg/dl by the time the patient was received in ICU. Postoperatively, the LVEF% reduced to 48.48 ± 50.8, post-operative TAPSE value reduced to 8 ± 2.6, while post-operative LVIDs was 15.49 ± 4.6, and LVIDd to 25.66 ± 6.1. Postoperative Hb reduced to 11.91 ± 1.5, platelets to 150.24 ± 66.9, PT to 12.65 ± 3.2, APTT to 26.27 ± 6, INR to 1.19 ± 0.3. The average amount of blood was 48.6 ml/kg/hour. Reason for postoperative bleeding were surgical complications, coagulation disorders, medications, surgical technique, patient's health, infection, and postoperative Care. Conclusion: Postoperative bleeding is a common and serious complication in patients with congenital heart undergoing open cardiac surgery and is a major threat to the patient’s postoperative morbidity and mortality. It also indirectly has a strong impact on the resources utilized towards the patient along with the financial, emotional burden on the families. This study would help us to identify the correctable risk factors which will help in improving the overall outcome of post-operative patients. Keywords: congenital heart disease, hemoglobin, hematocrit, postoperative bleeding